# Answer to Question #16770 in Discrete Mathematics for nelly

Question #16770

let A be{1,2,3,4,11} let B be{2,4,5,6,9} and C be {1,3,7,8,10}

find 1.(A-B)-C

2.(A-C)-(B-C)

3.is (A-B)-C=(A-C)-(B-C)

find 1.(A-B)-C

2.(A-C)-(B-C)

3.is (A-B)-C=(A-C)-(B-C)

Expert's answer

1. (A-B)-C

we must find at first (A-B) its the set of elements that belongs

to A but not to B

(A-B)={1,3,11}

then (A-B)-C that elements that in the

(A-B) but not in C

(A-B)={1,3,11}, C={1,3,7,8,10} and we see that

(A-B)-C={11}

2. (A-C)-(B-C) we must find (A-C) and (B-C) in the such way

as in the 1.

D=(A-C)={2,4,11}

E=(B-C)={2,4,5,6,9}

and now we find

(A-C)-(B-C)=D-E

and D-E={11}

3. we see that (A-B)-C=(A-C)-(B-C)

we must find at first (A-B) its the set of elements that belongs

to A but not to B

(A-B)={1,3,11}

then (A-B)-C that elements that in the

(A-B) but not in C

(A-B)={1,3,11}, C={1,3,7,8,10} and we see that

(A-B)-C={11}

2. (A-C)-(B-C) we must find (A-C) and (B-C) in the such way

as in the 1.

D=(A-C)={2,4,11}

E=(B-C)={2,4,5,6,9}

and now we find

(A-C)-(B-C)=D-E

and D-E={11}

3. we see that (A-B)-C=(A-C)-(B-C)

## Comments

## Leave a comment